Lord of the ring - Nik Ahmad Shaiffudin, Nik Him; Nik Arif, Nik Mohamad; Rosliza, Yahaya; Azizul Fadzli, Jusoh; Amirah, A Rashid; Mohd Lotfi, Hamzah (2018)
Emergency care provider (ECP) managing schizophrenia will deal with many challenges, not only during acute clinical management but also post discharged from Emergency Department (ED). Failure to anticipate the possible risk or harm will cause an unnecessary permanent injury resulting in a substandard management of the patient and even death.